Surgery combined with intra-operative microwaves ablation for the management of colorectal cancer liver metastasis: A case-matched analysis and evaluation of recurrences - Guadagni, Simone; Marmorino, Federica; Furbetta, Niccolò; Carullo, Martina; Gianardi, Desirée; Palmeri, Matteo; Di Franco, Gregorio; Comandatore, Annalisa; Moretto, Roberto; Cecilia, Elisa; Dima, Giovanni; Masi, Gianluca; et al. (Frontiers in Oncology, 2022)
Background Hepatic resection is the only chance of cure for a subgroup of patients with colorectal cancer liver metastasis. As the oncologic outcomes of intra-operative microwaves ablation combined with hepatic resection still remain uncertain in this setting, we aimed to compare this approach with surgery alone in patient’s candidate to metastases resection with radical intent. Methods Using a case-matched methodology based on age, gender, American Society of Anesthesiology score, Body Mass Index, and burden that take in consideration the number and maximum size of lesions, 20 patients undergoing hepatic resection plus intra-operative microwaves (SURG + IMW group) and 20 patients undergoing hepatic resection alone (SURG group), were included. Relapse-free Survival and post-resection Overall Survival were compared between patients of two groups. Results At the median follow up of 22.4 ± 17.8, 12/20 patients (60%) in SURG +IMW group and 13/20 patients (65%) in the SURG group experienced liver metastasis recurrence (p=0.774). None of them had recurrence at the same surgical or ablation site of the first hepatic treatment. 7/12 patients in the SURG+IMW group and 7/13 patients in the SURG group underwent at least one further surgical treatment after relapse (p = 1.000). No difference was reported between the two groups in terms of Relapse-free Survival (p = 0.685) and post-resection Overall Survival (p = 0.151). The use of intra-operative microwaves was not an independent factor affecting Relapse-free Survival and post-resection Overall Survival at univariate and multivariate analysis. Conclusions Patients with colorectal cancer liver metastasis undergoing surgery plus intra-operative microwaves have similar post-operative results compared with surgery alone group. The choice between the two approaches could be only technical, depending on the site, number, and volume of the metastases. This approach could also be used in patients with liver metastasis relapse who have already undergone hepatic surgery.